(untitled) (Acta Scientiarum. Agronomy, 2015)
This study aims to evaluate the phytotoxicity potential of leaf and root extracts of Drimys brasiliensis on the germination and seedling growth of Panicum maximum and Euphorbia heterophylla and its influence on metaxylem cell size in the seedling roots of the latter specie. The leaf and root extracts were fractionated by partition chromatography, and the hexane and ethyl acetate fractions obtained from each organ were evaluated at different concentrations for phytotoxic activity in several bioassays. In seedling growth tests, we compared the effects of these fractions with the herbicide oxyfluorfen. The hexane fraction of the root extracts showed a higher inhibitory potential on the germination and growth of weeds and reduced the average size of the metaxylem cells of E. heterophylla roots by more than 50%.The inhibitory effects of the root hexane fraction on seedling growth was similar to the herbicide, indicating that D. brasiliensis is a possible alternative form of control for the weed species examined.